Crushed little stars: A Praxis-in-Process of Black Girlhood. Issue 2 (1st June 2021) - Ealey, Jordan
Abstract: This is a performative engagement with the theory and practice of Black girlhood. I begin with an excerpt from my play-in-process, crushed little stars, which is itself a meditation on the sad Black girl. I share this process of play not only to present play making as a powerful epistemological tool, but also to blur the boundaries between what constitutes theory as opposed to practice. I (re)imagine Black girl sociality as a site of restoration and healing against the racist, sexist, and ageist world with which Black girls are forced to contend. Accordingly, this project contributes to the diversification of girlhood studies, challenging the disciplinarity of the field by extending ethnographic and sociological perspectives to include the vantage point of performance and creative practice.